2021
DOI: 10.1017/s0954579421000584
|View full text |Cite
|
Sign up to set email alerts
|

Self-control and cooperation in childhood as antecedents of less moral disengagement in adolescence

Abstract: Moral disengagement is a social cognition people use to engage in wrongdoings even when they know it is wrong. However, little is known about the antecedents that predict moral disengagement. The current study focuses on the development of self-control and cooperation during middle childhood as two antecedents of moral disengagement among 1,103 children (50% female; 77% White, 12% Black, 6% Hispanic, and 5% other). Children's self-control at age 8 and growth in self-control from age 8 to 11 were positively lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…These processes may be related to rapid changes in self‐control which may be difficult to capture without very frequent measurements along this period. A few previous studies in the field have shown more frequent measurements of self‐control along preadolescence to early adolescence (e.g., NICHD SECCYD: Gülseven, Liu, et al., 2021; Gülseven, Yu, et al., 2021), but lacked the genetical perspective which the current study provides. Future twin studies with more measurement points (e.g., each year, or every 6 months) along preadolescence to early adolescence may shed more light on this matter.…”
Section: Discussionmentioning
confidence: 78%
“…These processes may be related to rapid changes in self‐control which may be difficult to capture without very frequent measurements along this period. A few previous studies in the field have shown more frequent measurements of self‐control along preadolescence to early adolescence (e.g., NICHD SECCYD: Gülseven, Liu, et al., 2021; Gülseven, Yu, et al., 2021), but lacked the genetical perspective which the current study provides. Future twin studies with more measurement points (e.g., each year, or every 6 months) along preadolescence to early adolescence may shed more light on this matter.…”
Section: Discussionmentioning
confidence: 78%
“…In line with the organism–environment interaction model, adolescents who are bound to groups conducive to deviance and have low self‐control are more likely to develop MD. One possible explanation is that high self‐control adolescents have internalized more moral values and have more standards in their moral understanding, and a mature moral self‐identity (Gülseven et al, 2021). Thus, they are less likely to have MD.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, adolescents with low self‐control are more likely to be short‐sighted, self‐centered, and risk‐seeking and more biased toward minimizing adolescents' responsibility in aggressive behaviors. Therefore, they are more likely to lose control and bully others online compared with adolescents with high self‐control, even if they have similar levels of MD (Gülseven et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Early attempts to study the relation between attitudes towards certain moral principles or standards (like respect, justice, benevolence; as measured through self-report questionnaires) and specific cooperative behaviors found, as an overall result, that these behaviors are difficult to predict from such global attitudes 9 (which confirms the general finding in social psychology known as the attitude-behavior inconsistency 10 ). On the other hand, studies that focused on specific moral constructs have shown that inducing moral emotions like gratitude and guilt increases cooperation [11][12][13][14] and that moral disengagement correlates negatively with cooperative behavior 15,16 .…”
Section: Introductionmentioning
confidence: 99%